Genetic Characterization and Comparative Genome Analysis of Brucella melitensis Isolates from India. (25th July 2016) - Azam, Sarwar; Rao, Sashi Bhushan; Jakka, Padmaja; NarasimhaRao, Veera; Bhargavi, Bindu; Gupta, Vivek Kumar; Radhakrishnan, Girish
Abstract : Brucellosis is the most frequent zoonotic disease worldwide, with over 500, 000 new human infections every year. Brucella melitensis, the most virulent species in humans, primarily affects goats and the zoonotic transmission occurs by ingestion of unpasteurized milk products or through direct contact with fetal tissues. Brucellosis is endemic in India but no information is available on population structure and genetic diversity of Brucella spp. in India. We performed multilocus sequence typing of four B . melitensis strains isolated from naturally infected goats from India. For more detailed genetic characterization, we carried out whole genome sequencing and comparative genome analysis of one of the B . melitensis isolates, Bm IND1. Genome analysis identified 141 unique SNPs, 78 VNTRs, 51 Indels, and 2 putative prophage integrations in the Bm IND1 genome. Our data may help to develop improved epidemiological typing tools and efficient preventive strategies to control brucellosis.